Bought and Sold
An Investigative Documentary About the International Trade in Women. Based on a two-year undercover investigation, Bought & Sold documents the illegal trafficking in women for forced prostitution out of Russia and the Former Soviet Union and into Europe, Asia and the United States. Global Survival Network staff went undercover in meetings with the Russian mafia and in brothels around the world to get an insider's perspective on how the international trade in women works. This groundbreaking documentary helped to catalyze legislative reform on trafficking worldwide, as well as new financial resources to address the problem. Produced and directed by current WITNESS Executive Director Gillian Caldwell. Funded by Open Society Institute, Soros Foundation; Echoing Green Foundation etc.